ИСПОЛЬЗОВАНИЕ НОТНОГО РЕДАКТОРА «SIBELIUS» ДЛЯ АКТИВИЗАЦИИ И ИНТЕНСИФИКАЦИИ ПРОЦЕССА ОБУЧЕНИЯ СТУДЕНТОВ МУЗЫКАЛЬНОГО НАПРАВЛЕНИЯ - Абылова, Г.Ж. (SCIENCE and SOCIETY, 2017)
The article deals with the effective use of the musical editor for the revitalization and intensification of the learning process of students of musical direction . The study of the computer program «Sibelius» helps students to absorb the skills and abilities better that needed in the future professional activity.
Keywords: computer technologies; education forms; intensification; activity; stave; stave editor; program Sibelius